Energy Sector Baseline Study in the Kakuma-Kalobeyei Refugee-Hosting Area in Kenya - International Finance Corporation (World Bank, Washington, DC, 2022)
Kakuma as a marketplace, a 2018 consumer and market study of Kakuma refugee camp in northwest Kenya, estimates that Kakuma camp and its hosting community have 2,100 refugee-owned businesses and are worth 56 million dollars based on household consumption. This study provides information for businesses in the energy sector to help them assess opportunities for providing or expanding energy services in the Kakuma and Kalobeyei areas; it also provides insights to inform International Finance Corporation (IFC) interventions. The study maps the supply of and demand for energy for lighting, cooking, and productive use among households and businesses in the camp and examines the regulatory environment affecting the energy sector.